ESKİ ARAPGİR (MALATYA) CİVARINDAKİ MİYO-PLİYOSEN BİRİMLERİN KİL MİNERALOJİSİ VE JEOKİMYASI - BAYTAŞOĞLU, ZEYNEP (Fırat Üniveristesi, 2011)
Çalışmada Alibona Formasyonu alt seviyeleri, üst seviyeleri ve Malatya Volkanitleri'yle girik durumda bulunan göl çökellerinden örnekleme yapılarak, çökellerin mineraloji ve jeokimyasının belirlenmesi amaçlanmaktadır.

The Permo-Triassic Keban Metamorphics are characterized by marble with schists. Alibonca Formation overlies Keban Metamorphics with angular unconformities, and represented by shallow marine clayey-carbonates and altered tuffs. Malatya Volcanics and volcano-sedimantary units show gradial transition to Alibonca, and have thick tuff levels, basaltic lavas and cherty limestones. Goal of this study 1-Ascertain of mineralogy and geochemistry of lower and upper levels of marine Alibonca Formation and Malatya lacustrine formation.
Old Arapgir (Malatya) mio-pliocene age around clay mineralogy and geochemistry of the units
Keywords: Jeoloji Mühendisliği